Ovarian Sertoli-Leydig Cell Tumors: Epidemiological, Clinical and Prognostic Factors - Castro, Beatriz Guerreiro Ruiz; Souza, Cristiano de Pádua; Andrade, Carlos Eduardo Mattos da Cunha; Vieira, Marcelo de Andrade; Andrade, Diocésio Alves Pinto de; Reis, Ricardo dos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To describe a series of cases of ovarian Sertoli-Leydig cell tumors (SLCTs).Methods Retrospective review of 12 cases of SLCT treated at the Hospital do Câncer de Barretos, Barretos, state of São Paulo, Brazil, between October 2009 and August 2017.Results The median age of the patients was 31 years old (15–71 years old). A total of 9 patients (75.0%) presented symptoms: 8 (66.7%) presented with abdominal pain, 5 (41.7%) presented with abdominal enlargement, 2 (16.7%) presented with virilizing signs, 2 (16.7%) presented with abnormal uterine bleeding, 1 (8.3%) presented with dyspareunia, and 1 (8.3%) presented with weight loss. The median preoperative lactate dehydrogenase (LDH) was 504.5 U/L (138–569 U/L), alpha-fetoprotein (AFP) was 2.0 ng/ml (1.1–11.3 ng/ml), human chorionic gonadotropin (β-hCG) was 0.6 mUI/ml (0.0–2.3 mUI/ml), carcinoembryonic antigen (CEA) was 0.9 ng/ml (0.7–3.4 ng/ml), and cancer antigen 125 (CA-125) was 26.0 U/ml (19.1–147.0 U/ml). All of the tumors were unilateral and surgically treated. Lymphadenectomy was performed in 3 (25.0%) patients, but none of the three patients submitted to lymphadenectomy presented lymph node involvement. In the anatomopathological exam, 1 (8.3%) tumor was well-differentiated, 8 (66.7%) were moderately differentiated, and 3 (25.0%) were poorly differentiated. A total of 5 (55.6%) tumors were solid-cystic, 2 (22.2%) were purely cystic, 1 (11.1%) was cystic with vegetations, and 1 (11.1%) was purely solid, but for 3 patients this information was not available. The median lesion size was 14.2 cm (3.2–23.5 cm). All of the tumors were at stage IA of the 2014 classification of the International Federation of Gynecology and Obstetrics (FIGO). A total of 2 (16.7%) patients received adjuvant treatment; 1 of them underwent 3 cycles of paclitaxel and carboplatin every 21 days, and the other underwent 4 cycles of ifosfamide, cisplatin and etoposide every 21 days. None of all of the patients had recurrence, and one death related to complications after surgical staging occurred.Conclusion Abdominal pain was the most frequent presentation. There was no ultrasonographic pattern. All of the SLCTs were at stage IA, and most of them were moderately differentiated. Relapses did not occur, but one death related to the surgical staging occurred.
Keywords: ovarian neoplasms; Sertoli-Leydig cell tumor; oncologic prognosis